Heart failure increases atrogin-1 and MuRF1 gene expression in skeletal muscle with fiber type-specific atrophy - Carvalho, Robson Francisco [UNESP]; Castan, Eduardo Paulino [UNESP]; Coelho, Cesar Augusto [UNESP]; Lopes, Francis Silva; Alves Almeida, Fernanda Losi [UNESP]; Michelin, Aline [UNESP]; Alves de Souza, Rodrigo Wagner [UNESP]; Araujo, Joao Pessoa [UNESP]; Cicogna, Antonio Carlos [UNESP]; Dal Pai-Silva, Maeli [UNESP] (Springer, 2010)
Heart failure (HF) is characterized by a reduced tolerance to exercise due to early fatigue and dyspnea; this may be due in part to skeletal muscle myopathy with a shift from slow to fast fibers and loss of muscle mass. Muscle wasting does not occur similarly in all types of muscle fiber, thus we tested the hypothesis that HF induces skeletal muscle atrophy in a fiber type-specific manner altering the expression of atrogin-1 and MuRF1 in a fast muscle of rats with monocrotaline-induced heart failure. We studied extensor digitorum longus (EDL) muscle from both HF and control Wistar rats. Atrogin-1 and MuRF1 mRNA content were determined using Real-Time RT-qPCR while muscle fiber cross-sectional area (CSA) from sections stained histochemically for myofibrillar ATPase were used as an index of type-specific fiber atrophy. The measurement of gene expression by RT-qPCR revealed that EDL muscle mRNA expression of MuRF1 and atrogin-1 was significantly increased in the HF group. Muscle fiber type IIB CSA decreased in the HF group compared to the CT group; there was no significant difference in muscle fiber types I and IIA/D CSA between the HF and CT groups. In conclusion, we showed that HF induces fiber type IIB specific atrophy, up-regulating atrogin-1 and MuRF1 mRNA expression in EDL muscle of monocrotaline treated rats.
Keywords: Atrogin-1; MuRF1; Fiber Type-Specific Atrophy